ANALYSIS OF THE INFLUENCE OF CASH ON DELIVERY (COD), SERVICE QUALITY, DELIVERY ACCURACY, AND TRUST ON CUSTOMER DECISIONS USING J&T COURIER - Rahmad Firdaus; Fithriawan Nugroho; Mat Amin; Ririn Saputra (Jurnal Ekonomi, 2023)
The objective of this study is to examine how Cash on Delivery (COD), Service Quality, Delivery Accuracy, and Trust influence customer decisions when utilizing J&T Expeditions. The research adopts an explanatory approach with a quantitative method, establishing causal relationships between variables. The research model involves hypothesis testing to assess the researcher's proposed theoretical connections. The data used consists of primary and secondary data, gathered from 100 research participants who are consumers of J&T Expeditions. Multiple linear regression analysis is employed as the data analysis technique. The findings indicate that cash on delivery (COD), service quality, delivery accuracy, and trust positively and significantly influence customer decisions to utilize J&T Expeditions.